Adenosine Receptors as a Biological Pathway for the Anti-Inflammatory and Beneficial Effects of Low Frequency Low Energy Pulsed Electromagnetic Fields. (1st February 2017) - Varani, Katia; Vincenzi, Fabrizio; Ravani, Annalisa; Pasquini, Silvia; Merighi, Stefania; Gessi, Stefania; Setti, Stefania; Cadossi, Matteo; Borea, Pier Andrea; Cadossi, Ruggero
Abstract : Several studies explored the biological effects of low frequency low energy pulsed electromagnetic fields (PEMFs) on human body reporting different functional changes. Much research activity has focused on the mechanisms of interaction between PEMFs and membrane receptors such as the involvement of adenosine receptors (ARs). In particular, PEMF exposure mediates a significant upregulation of A 2 A and A3 ARs expressed in various cells or tissues involving a reduction in most of the proinflammatory cytokines. Of particular interest is the observation that PEMFs, acting as modulators of adenosine, are able to increase the functionality of the endogenous agonist. By reviewing the scientific literature on joint cells, a double role for PEMFs could be hypothesized in vitro by stimulating cell proliferation, colonization of the scaffold, and production of tissue matrix. Another effect could be obtained in vivo after surgical implantation of the construct by favoring the anabolic activities of the implanted cells and surrounding tissues and protecting the construct from the catabolic effects of the inflammatory status. Moreover, a protective involvement of PEMFs on hypoxia damage in neuron-like cells and an anti-inflammatory effect in microglial cells have suggested the hypothesis of a positive impact of this noninvasive biophysical stimulus.